Strengthening the family economy through fruit processing business into healthy syrup in Empowered Women's Community - Taufik Akbar; Restu Jati Saputro; Erlyn Rosalina; Iklima Ermis Ismail (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
The Covid-19 pandemic has a direct impact on the income of the Indonesian people. As many as 84% of people feel a decrease in income. Community Service Activities aim to help improve the knowledge and skills of women who are members of the Community of Empowered Women’s and Family Welfare Programme (PKK) Women’s of Perum Grand Asri Cikarang, to process fresh fruit into healthy syrup without preservatives, dyes, flavors, and artificial sweeteners. The method of implementing activities is in the form of training and mentoring to create product innovations and conduct product marketing digitally. The activities carried out included information transfer, training on fruit processing into syrup, making product designs with the SICIKA brand, creation of product promotion content using the AIDA method, and mentoring to make ready-to-sell products. The result of this community service activity is an increase in partner skills in making syrup products with the SICIKA brand and digital marketing promotional content for the sale of these products.